Perbaikan profil lipid pada perempuan dewasa kelebihan berat badan setelah intervensi sari jeruk kalamansi (Citrus microcarpa) - Surlitah, Sutemy; Setiawan, Budi; Briawan, Dodik (Jurnal Gizi dan Pangan, 2017)
The objective of this research was to analyze the effect of calamansi juice intervention on lipid profiles of overweight adult women. The pre-post and randomized single-blinded clinical study were applied on 24 subjects who were randomly and alocated into two group, i.e group A (300 ml 100% pure calamansi juice) and group B (300 ml and 50% concentrante calamansi juice). The juice was given twice a day (each 150 ml) for 28 days and lipid profiles were analyzed before and after intervention. The result showed a significant decrease (p<0.05) after intervention in Triglyseride plasma (TG) level (-23.67±21.81 and -2.33±22.39 mg/dl), low density lipoprotein (LDL-c) -30.58±25.05 and 12.42±26.66 mg/d), total cholesterol (TC) 23.50±30.90 and 12.00±30.80 mg/dl and a significant increase (p<0.05) in high density lipoprotein (HDL-c) plasma level (10.25±11.91 and 0.33±8.57 mg/dl). Meanwhile, in group B there was no significant change in lipid profiles. The intervention of 300 ml pure calamansi juice improved the lipid profile of overweight women.